2020
DOI: 10.3390/nano10091797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasonication Time on the Properties of Polyvinyl Alcohol/Sodium Carboxymethyl Cellulose/Nano-ZnO/Multilayer Graphene Nanoplatelet Composite Films

Abstract: Ultrasonication-assisted solution casting was used to prepare polyvinyl alcohol (PVA)/sodium carboxymethyl cellulose (CMC)/nano-ZnO/multilayer graphene nanoplatelet (xGnP) composite films; the performances (mechanical properties, water vapor permeability (WVP), biodegradability and antibacterial activity) of these films were investigated as a function of the ZnO NPs:xGnP mass ratio and ultrasonication time. Intermolecular interactions among ZnO NPs, xGnP and the PVA/CMC matrix were shown to improve WVP, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 63 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, sonication also enhanced the antimicrobial activities by the controlled generation of reactive oxygen species in the microbial cells [ 53 ]. Ji et al [ 54 ] found that the sonication of composite films more effectively inhibits the gram-negative bacteria than the gram-positive bacteria. This was mainly due to the strong interaction of S. aureus with the negatively charged reactive oxygen species (ROS) produced by sonication.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, sonication also enhanced the antimicrobial activities by the controlled generation of reactive oxygen species in the microbial cells [ 53 ]. Ji et al [ 54 ] found that the sonication of composite films more effectively inhibits the gram-negative bacteria than the gram-positive bacteria. This was mainly due to the strong interaction of S. aureus with the negatively charged reactive oxygen species (ROS) produced by sonication.…”
Section: Resultsmentioning
confidence: 99%
“…Beikzadeh et al [23] found that prolonged sonication could break down the polysaccharide chains and induce a new chemical bond, and therefore, a denser film network formed. Ji et al [24] reported that the extended sonication time had increased the composite film's color and transmittance.…”
Section: Color Characteristicsmentioning
confidence: 99%
“…Due to its superior mechanical properties, swelling ability, inexpensive cost, and greater number of constituents than pure CMC hydrogels, PVP/CMC blend hydrogel has a significant potential for application as a wound dressing [10,11]. PVP/CMC and PVP/CMC/BA hydrogels might work well for treating and healing wounds [12,13].…”
Section: Introductionmentioning
confidence: 99%